Efficacy of erythrocyte apheresis in the management of severe high-altitude deacclimatization syndrome: a retrospective cohort study - Wang, Xinmiao; Huang, Rong; Su, Chunrong; Yao, Hao; Zhang, Ling; Yang, Hui; Wang, Xiao; Su, Yi; Yi, Hai (Frontiers in Physiology, 2025)
BackgroundHigh-altitude deacclimatization syndrome (HADAS, commonly known as Oxygen toxicity) manifests through multi-organ system dysfunction and significantly deteriorates the quality of life. Unfortunately, there are no effective methods for serious HADAS (SHADAS) patients. To address this urgent public health challenge, we explored the therapeutic potential of erythrocyte apheresis (EA)-a technique previously used in HAPC treatment, and evaluated its efficacy in SHADAS patients.MethodsThis retrospective cohort study analyzed clinical data of 71 SHADAS patients undergoing EA between October 2016 and September 2024 in our hematology department. Complete blood count parameters were serially measured before and after EA. Data analysis was performed using GraphPad Prism 8.02 software.ResultsThe study cohort exhibited significant reductions in hemoglobin (HGB) levels after initial EA: HGB decreased from 224.75 ± 12.76 g/L to 172.92 ± 22.60 g/L (males, P < 0.001) and from 205.13 ± 12.41 g/L to 164.75 ± 19.26 g/L (females, P < 0.001). Notably, 18 patients required repeat EA due to suboptimal response, and these patients had higher HGB baseline levels. (HGB 238.47 ± 8.76 vs 219.67 ± 9.98 g/L). All subjects demonstrated marked symptomatic improvement in SHADAS manifestations including headache, somnolence, and fatigue after EA. Based on these findings, we developed a strategy for the formulation of EA parameter protocols.ConclusionAlthough it remains challenging to prevent SHADAS in individuals transitioning to lower altitude regions, our study demonstrated that EA could rapidly reduce HGB and alleviate associated symptoms. Moreover, we have established the parameters of EA in the treatment of SHADAS.